Patient's preference for sacrospinous hysteropexy or modified Manchester operation: A discrete choice experiment. (31st August 2022) - Schulten, Sascha F. M.; Essers, Brigitte; Notten, Kim J. B.; Enklaar, Rosa A.; van Leijsen, Sanne A. L.; van Eijndhoven, Hugo W. F.; Kluivers, Kirsten B.; Weemhoff, Mirjam
Abstract: Objective: To investigate women's preference for modified Manchester (MM) or sacrospinous hysteropexy (SH) as surgery for uterine prolapse. Design: Labelled discrete choice experiment (DCE). Setting: Eight Dutch hospitals. Population: Women with uterine prolapse, eligible for primary surgery and preference for uterus preservation. Methods: DCEs are attribute‐based surveys. The two treatment options were labelled as MM and SH. Attributes in this survey were treatment success ( levels SH: 84%, 89%, 94%; levels MM: 89%, 93%, 96%), dyspareunia (levels: 0%, 5%, 10%), cervical stenosis (levels: 1%, 6%, 11%) and severe buttock pain (levels: 0%, 1%). A different combination of attribute levels was used in each choice set. Women completed nine choice sets, making a choice based on attribute levels. Data were analysed in multinomial logit models. Main outcome measures: Women's preference for MM or SH. Results: 137 DCEs were completed (1233 choice sets). SH was chosen in 49% of the choice sets, MM in 51%. Of all women, 39 (28%) always chose the same surgery. After exclusion of this group, 882 choice sets were analysed, in which women preferred MM, likely associated with a labelling effect, i.e. description of the procedure, rather than the tested attributes. In that group, MM was chosen in 53% of the choice sets and SH in 47%. When choosing MM, next to the label, dyspareunia was relevant for decision‐making. For SH, all attributes were relevant for decision‐making. Conclusions: The preference of women for MM or SH seems almost equally divided. The variety in preference supports the importance of individualised healthcare. Abstract : This article includes Author Insights, a video abstract available at: https://vimeo.com/736147808